Management of Rhizome Rot Disease of Ginger (Zingiber officinale rose L.) - Srivastva; N. K. Sharma, A. K. Pandey, L. P. Awasthi, J. P. (Journal of Phytology, 2010)
Ginger (Zingiber officinale rose L.) is an important spice crop belonging to family Zingiberaceae. Rhizome rot of ginger, caused by Pythium aphanidermatum (Edson) Fitz, is a major constraint for the production of healthy rhizome, sometimes causing total failure of crop. Chemical control of this pathogen is not economical because of high cost of chemicals, breake down of resistance, environmental pollution, deleterious effect to non target beneficial soil micro-organism and ultimately the choice of the consumer for a organic product. Thus the treatment with plant products (Boerhaavia diffusa root extract) may offer a practical and economical alternative for eco-friendly management of this disease. Rhizomes dipped overnight in the suspension of 10.00 per cent crude root extractÂ followed by 3 foliar sprays of the same proved quite effective in the management of the disease. Results indicated a gradual decrease in disease incidence with the corresponding increase in number of sprays and rhizome treatment with B. diffusa root extract. Key words: Ginger, Pythium aphanidermatum, rot of ginger <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">A. K. Pandey et al. Management of Rhizome Rot Disease of Ginger (Zingiber officinale rose L.). J Phytol 2/9 (2010) 18-20.